1999
DOI: 10.1002/1529-0131(199911)42:11<2410::aid-anr20>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus stimulates inducible nitric oxide synthase in articular cartilage

Abstract: Objective. To determine if Staphylococcus aureus stimulates the L-arginine-nitric oxide (NO) synthase pathway in articular cartilage. Methods. A heat-killed and sonicated (denatured) S aureus preparation was added to cultures of bovine articular cartilage. NO production was measured as accumulated nitrite in the culture medium and by the NO synthase-dependent conversion of 3 H-L-arginine to 3 H-L-citrulline in cartilage homogenates. Inducible NO synthase (iNOS) messenger RNA (mRNA) expression was analyzed by N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Three discs were placed in each well of 24‐well plates (1 ml final volume). Chondrocytes were isolated from cartilage by collagenase digestion [20] and plated in 25‐cm 2 flasks (5×10 5 ) containing Dulbecco's modified essential medium (DMEM) supplemented with 10% foetal bovine serum. Primary chondrocyte monolayer cultures and cartilage explants were incubated at 37°C in a 5% CO 2 humidified atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Three discs were placed in each well of 24‐well plates (1 ml final volume). Chondrocytes were isolated from cartilage by collagenase digestion [20] and plated in 25‐cm 2 flasks (5×10 5 ) containing Dulbecco's modified essential medium (DMEM) supplemented with 10% foetal bovine serum. Primary chondrocyte monolayer cultures and cartilage explants were incubated at 37°C in a 5% CO 2 humidified atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Cartilage destruction in septic arthritis is usually attributed to the direct toxic effect of S. aureus on chondrocytes . In addition, several studies have shown that release of cytokines and proteases as a result of S. aureus infection leads to acute degradation of cartilage extracellular matrix (ECM) within even a few days . However, one major frustration in treating bacterial arthritis in clinic is that, despite eradication of bacteria from the joint cavity, destruction of the joint cartilage triggered by an acute S. aureus infection often continues, resulting in permanent joint damage with persistent expression of catabolic factors including matrix metalloproteinases (MMPs) and inducible NO synthase (iNOS) .…”
mentioning
confidence: 99%